2017
DOI: 10.18869/acadpub.ihepsaj.5.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Pap Smear Preventive Behavior among Women Based on Health Belief Model: A Qualitative Study

Abstract: Background and objective: Cervical cancer is one of the most prevalent cancers among women. Although Pap smear test is an effective screening program, it is not conducted very frequently. This study aimed to recognize the determinants affecting women's participation in Pap smear test screening, with a qualitative approach, based on the health belief model (HBM). Materials and methods:This was a qualitative research, based on thematic analysis, conducted in 2015. Participants were 30 rural women who participate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
4
10
0
Order By: Relevance
“…The high cost of the test reduces individuals' willingness to do it. Consistent with our findings, women participating in the Bahmani et al (2017) and Nazari (2019) studies have identified financial problems as one of the main barriers to doing the test [ 54 , 55 ]. Financial constraints and economic issues related to PS screening reported in other studies have also been a barrier to performing the screening [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The high cost of the test reduces individuals' willingness to do it. Consistent with our findings, women participating in the Bahmani et al (2017) and Nazari (2019) studies have identified financial problems as one of the main barriers to doing the test [ 54 , 55 ]. Financial constraints and economic issues related to PS screening reported in other studies have also been a barrier to performing the screening [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…The fatalism was the last finding of the present study and women were not afraid of being at risk of the disease and subsequent death. The results of several studies have been consistent with those of the present study, and religious beliefs, such as that disease and healing are God's will, have been identified as a barrier to preventive interventions for cervical cancer [ 54 , 69 , 75 ]. In appreciative fatalists, the belief that cancer is a person's fate and nothing can be done to prevent it, delays and challenges the process of diagnosing and treating cervical cancer, and proper planning and interventions must be designed and implemented to correct this belief.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations